ANALISIS GAP PADA PERSIMPANGAN JALAN DI KOTA PONTIANAK - Apriansyah, Dani; Suyono, Rudi S.; Azwansyah, Heri (Jurnal Mahasiswa Teknik Sipil Universitas Tanjungpura, 2018)
At the intersection form of three arms that have a flow of traffic is not a priority system / primary right, the flow of traffic out of the sleeve intersection perpendicular arms intersection others, will find it difficult to merge (merging) with the flow of arms Other adverse, adversity is due to lack of sufficient gap deemed adequate by the driver, to carry out infiltration. With such conditions it happen cause actual barriers that long queue at the foot of the perpendicular intersection. This study aims to determine whether the intersection of Kom Yos Soedarso Street and Tebu Sreet is still capable of delivering the volume of vehicles passing through the intersection by using Method Gap Acceptance. This study begins with the collection of traffic flow data movement for 3 days involving six surveyors to obtain data on the volume of traffic for 13 hours and video cameras to obtain the data gap, which will be processed with the help of computer software. Furthermore, the data volume, which is acceptable gap and gap declined driver of minor roads are used to evaluate the critical values and to determine the probability of the vehicle from minor road which can be joined to the main road flows. Based on analysis of Gap Acceptance by the headway distribution calculation obtained the greatest opportunity of vehicles that can perform the movement broke into the main road safely is on Thursday at 12:00 to 13:00 there is a chance of some 225. On Saturday at 14:00 to 15:00 there are 263 vehicles. While on Sunday at 12:00 to 13:00 for 264 vehicles. The number of opportunities this vehicle is still greater than the number of minor traffic volume turn right. With these results concluded that the present condition of the intersection of Jalan Yos Kom Soedarso and Jalan Tebu still feasible without traffic arrangements.Â Keywords :Â  Gap Acceptance, Gap Critical, Headway Distribution